Silver for hard times: Supplying the Venetian mint, c. 1620-1640 - Isabella Cecchini (The Journal of European Economic History (JEEH), 2025)
This article examines the bullion and cash supply networks exploited by a pre-industrial government in times of financial, economic and material distress. The case study focuses on the monetary policy of the Republic of Venice and on the decisions taken by the main deliberative body, the Senate, for the acquisition of metals to be minted and reales - the silver coins minted by the Spanish in the Americas and circulated worldwide. The period under study (c.1620-1640) was marked by an increasing fiscal pressure, the beginning of prolonged financial difficulties, high military expenditure, recurring famines in the Venetian mainland which led to state intervention in the distribution of grain, and periodic epidemics culminating in the severe plague of 1630-1631. In response to the growing demand for Spanish reales, which had become virtually the only currency accepted in Levantine ports and able to pay for Venetian maritime forces, the Senate limited direct purchases through merchant-bankers who sourced silver from markets, notably from Genoese exporters. Instead, it relied heavily on the substantial reserves held in the Mint and redirected tax revenues from mainland territories to maritime offices. Based on a thorough examination of the Senate's decrees on mint operations, the study argues that the small group of public contractors supplying bullion and reales were able to negotiate as oligopolists with the Venetian government, which was compelled to turn to them only when reserves were depleted or reached a critical threshold; the sporadic recourse to these purchases, on the other hand, also indicates good financial health of the government of the Republic, which from 1646 was able to engage a gruelling conflict with the Ottomans.
Keywords: 330; Silberstandard; Geldpolitik; Silber; Außenhandel; Venedig; Südamerika; Spanien